Socio-Economic Status as Predictor of Social Media Usage among Islamic Studies Students in Senior Secondary Schools in Badagry Division of Lagos state - Olaniyan-Shobowale, K. O.; Bamiro, N. B.; Salau, A. A.; Yahya, I. O. (International Journal of Educational Management, 2021)
The study investigates socio-economic status as predictor of social media usage among Islamic studies students in senior secondary schools in Badagry division of Lagos state. It employed the survey research design with a total sample of one hundred and fifty secondary school students. The data obtained for the study was analyzed with descriptive statistic, Pearson Product Moment Correlation (PPMC), t-test and ANOVA. The findings revealed among others that socio-economic status predict social media usage among Islamic studies students and gender difference didn't exist with reference to usage of social media among Islamic studies students. Based on the findings, it was recommended that school authority, counsellor and teachers should reorientate secondary school students on the use of other social media platforms to ensure it does not affect their academic performance negatively, social media marketing should be introduced into trade and entrepreneurship subject at secondary school level, and parent should avoid buying internet enable phones for their children in secondary school since it has been identified as one of the motivating factors that influence their use of social media during classroom instruction.